The social-psychological perspective on executive compensation: evidence from a two-tier board system - Anja Schwering; Friedrich Sommer; Florian Uepping; Sandra Winkelmann (Journal of Business Economics, 2021)
This paper investigates whether and how social-psychological mechanisms, namely reciprocity, demographic similarity, and similar experiences, affect CEO compensation packages with respect to the levels of total, fixed, and short- and mid-term compensation and the variable proportion of the compensation package. We use evidence from Germany as it is considered a prototype of a two-tier board system. Given the primary roles of both the CEO and the chair of the supervisory board, we especially highlight social-psychological mechanisms in the process leading to the final compensation package. Using a hand-collected sample of non-financial constituents of the German HDAX, we find that reciprocity can lead to a compensation package that is more favorable for the CEO. Results on similarity are ambivalent such that the effects of similarity on CEO compensation—both positive and negative—may depend on the dimension of similarity. Finally, the chair's CEO experience, both inside and outside the focal company, also plays an essential role in shaping CEO compensation. More specifically, CEO experience in general is associated with more favorable compensation. However, having a chair that has been CEO at the focal company correlates with less favorable compensation packages except for when the CEO has also been recruited internally.
Keywords: G30; M52; J33; 650; Executive compensation; Social-psychological mechanisms; Corporate governance; Two-tier board